EVALUATION AND SELECTION OF RAPESEED (B rassica napus L.) M UTANT LINES FOR YIELD PERFORMANCE USING AUGMENTED DESIGN - I. Ali; H. M. Ahmed; S. A. Shah (Journal of Animal and Plant Sciences, 2013)
The present study was undertaken to evaluate rapeseed mutants for yield and yield components at an early stage of entry selection in a non-replicated trial. Sixty five mutant entries were selected from gamma irradiated population of 1.0, 1.2 and 1.4 K Gys. and planted in augmented incomplete block design in four blocks. The data on days to 50% flowering, seed yield (kg ha-1), 1000 seed weight (g) and oil yield (kg ha-1) were recorded and analyzed to workout variance and contrast analyses. Significant differences were revealed for all the traits among the mutants and with the control except 1000-seed weight. Three mutant lines were significantly superior both in seed yield and oil yield. Ten mutant lines took significantly less number of days to 50% flowering. The study confirmed the effeciency of augmented design in the evaluation and selection of superior genotypes in early generation with better yield potential.
Keywords: Rapeseed; Gamma Rays; Non-Replicated; Augmented Design